Retinal ganglion cell desensitization is mitigated by varying parameter constant excitation pulse trains - Li, Wennan; Haji Ghaffari, Dorsa; Misra, Rohit; Weiland, James D. (Frontiers in Cellular Neuroscience, 2022)
Retinal prostheses partially restore vision in patients blinded by retinitis pigmentosa (RP) and age-related macular degeneration (AMD). One issue that limits the effectiveness of retinal stimulation is desensitization of the retina response to repeated pulses. Rapid fading of percepts is reported in clinical studies. We studied the retinal output evoked by fixed pulse trains versus pulse trains that have variable parameters pulse-to-pulse. We used current clamp to record RGC spiking in the isolated mouse retina. Trains of biphasic current pulses at different frequencies and amplitudes were applied. The main results we report are: (1) RGC desensitization was induced by increasing stimulus frequency, but was unrelated to stimulus amplitude. Desensitization persisted when the 20Hz stimulation pulses were applied to the retinal ganglion cells at 65 A, 85 A and 105 A. Subsequent pulses in the train evoked fewer spikes. There was no obvious desensitization when 2Hz stimulation pulse trains were applied. (2) Blocking inhibitory GABAA receptor increased spontaneous activity but did not reduce desensitization. (3) Pulse trains with constant charge or excitation (based on strength-duration curves) but varying pulse width, amplitude, and shape, increased the number of evoked spikes/pulse throughout the pulse train. This suggests that retinal desensitization can be partially overcome by introducing variability into each pulse.